The Characteristics of Seawater Environment and Geochemistry of Surface Sediment in Quang Binh Sea Area (60-100m Depth) - Hoang Van, Hiep; Nguyen, Nguyen Dinh; Dinh Thai, Nguyen; Van Tich, Vu; Viet Duc, Vu (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4309, 2018)
Abstract: The geochemical characteristics of seawater and surface sediment represent the stability of seawater quality. There is a lack of information on geochemical characteristics of elements in seawater well as sediment in the sea area of Quang Binh province. The objective of this paper is to study and determine the characteristics of the marine environment through elemental geochemistry in seawater and surface sediments of the Quang Binh area to assess the stability and quality of seawater in this area. The results show that seawater environment is characterized by a shallow sea with rare effect on continental water. The difference in salinity values, Eh, pH...at different depths are indistinguishable. The sedimentary environment is weak alkaline, the environment from decontamination to strong oxidation. Pb element distributed in seawater and Br, I elements distributed in surface sediment are mostly concentrated in the center of the study area. Keywords: Geochemical characteristics, distribution of elements, sediment characteristics. References [1] Prudente S. M., Ichihashi, H., and Tatsukawa, R., Heavy metal concentrationsin sediments from Manila bay, Philippines andinflowing rivers: Environmental Pollution, v. 86, (1994), 83-88. [2] Zhang L., Ye, X., Feng, H., Jing, Y.,Ouyang, T., Yu, X., Liang, R., Gao, C., and Chen,W., Heavy metal contamination in western Xiamen Bay sediments and its vicinity, China:Marine Pollution Bulletin, v.54, (2007), 974-982. [3] Zwolsman J., Van Eck, G., and Burger, G., Spatial and temporal distribution of trace metals in sediments from the Scheldt estuary,south-west Netherlands: Estuarine, Coastal andShelf Science, v.43, (1996) 55-79. [4] Nguyễn Biểu, Đào Mạnh Tiến và nnk, Báo cáo kết quả điều tra địa chất và tìm kiếm khoáng sản biển ven bờ (0-30m nước) miền Trung (Nga Sơn - Vũng Tàu), Lưu trữ TTĐCKS Biển, Hà Nội, 1995. [5] Nguyễn Biểu và nnk, Báo cáo tổng kết đề án Điều tra địa chất và tìm kiếm khoáng sản rắn vùng biển nông ven bờ (0 - 30 m nước) Việt Nam tỷ lệ 1/500.000, lưu trữ Cục Địa chất và Khoáng sản Việt Nam, Hà Nội, 2001. [6] Mai Trọng Nhuận, Đào Mạnh Tiến, Vũ Trường Sơn và nnk, Báo cáo thuyết minh bản đồ hiện trạng địa chất môi trường biển nông ven bờ (0-30m nước) miền Trung (Nga Sơn - Vũng Tàu). Lưu trữ TTĐCKS Biển, Hà Nội, 1995. [7] Mai Trọng Nhuận, Chu Văn Ngợi, Đào Mạnh Tiến và nnk,. Báo cáo thuyết minh bản đồ hiện trạng địa chất môi trường biển nông ven bờ (0-30m nước) Việt Nam tỷ lệ 1/500.000. Lưu trữ TTĐCKS Biển, Hà Nội, 2001. [8] Mai Trọng Nhuận và nnk, Báo cáo dự án “Điều tra đánh giá tích hợp và dự báo biến động điều kiện tự nhiên, tài nguyên, môi trường và tai biến thiên nhiên vùng biển từ Thanh Hóa đến Bình Thuận phục vụ phát triển kinh tế biển”, Hà Nội, 2012. [9] Mai Trọng Nhuận và nnk,. Báo cáo điều tra đặc điểm địa chất, địa động lực, địa chất khoáng sản, địa chất môi trường và dự báo tai biến địa chất vùng biển Việt Nam từ độ sâu 30 m nước đến độ sâu 100 m nước, tỷ lệ 1: 500.000. Lưu trữ TTĐCKS Biển, Hà Nội, 2011. [10] Trịnh Nguyên Tính và nnk, Báo cáo tổng kết Dự án thành phần: “Điều tra đặc điểm địa chất, địa động lực, địa chất khoáng sản, địa chất môi trường và dự báo tai biến địa chất vùng biển Việt Nam từ độ sâu 30m nước đến 100m nước, tỷ lệ 1:500.000, Lưu trữ ĐC, Hà Nội, 2012. [11] Nguyễn Biểu, Vũ Trường Sơn, Dương Văn Hải và nnk, Địa chất khoáng sản biển nông ven bờ (0-30 m nước) Việt Nam tỷ lệ 1/500.000. Lưu trữ địa chất, Hà Nội, 2001. [12] Đinh Văn Ưu, Hoàn lưu biển Đông, Biển Đông II, 319-356, Nhà xuất bản Đại học Quốc gia Hà Nội, Hà Nội, 2003. [13] Vinogradov A. P., Introduction in geochemistry of ocean, Moscow, Russian, Nauka, (1967), 142p.